2021
DOI: 10.1177/13623613211041189
|View full text |Cite
|
Sign up to set email alerts
|

Real-world executive functioning for autistic children in school and home settings

Abstract: Executive function challenges are commonly reported in the home setting for children with an autism spectrum disorder diagnosis (hereafter, autism), but little is known about these challenges in the school setting. A total of 337 youth (autism, N = 241 and typically developing, N = 96) were assessed using Behavior Rating Inventory of Executive Function ratings from home and school settings. Within each setting, we examined differences in specific executive function skills between diagnostic groups. Then, we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Students and employed participants reported having to themselves seek out support, self-initiate work, transition from work to leisure and between activities, sorting through general written information, planning and structuring work, and staying motivated throughout the day to a larger extent during the pandemic. Self-management functions may be particularly challenging for the general autism community [45] and many may need pedagogical support in everyday settings (including home-, school-, and work environments) relating to these challenges [7][8][9]. It is therefore not surprising that our participants found these particular demands caused distress and other negative outcomes.…”
Section: Negative Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Students and employed participants reported having to themselves seek out support, self-initiate work, transition from work to leisure and between activities, sorting through general written information, planning and structuring work, and staying motivated throughout the day to a larger extent during the pandemic. Self-management functions may be particularly challenging for the general autism community [45] and many may need pedagogical support in everyday settings (including home-, school-, and work environments) relating to these challenges [7][8][9]. It is therefore not surprising that our participants found these particular demands caused distress and other negative outcomes.…”
Section: Negative Outcomesmentioning
confidence: 99%
“…The distinctive diagnostic features and functional impairments are associated with a preference for highly predictable environments [3]. Conversely, change, unpredictability, and uncertainty are circumstances under which autistic individuals may respond with significant emotional and behavioral distress [7][8][9][10][11][12]. Moreover, caregivers of autistic children experience higher levels of stress than other groups of parents during pre-pandemic conditions [13] relating to the lifelong needs of their child, parents' pivotal role in advocacy, care coordination and provision, as well as typically variable access to targeted formal support [14].…”
Section: Introductionmentioning
confidence: 99%
“…Teacher‐reported sensory processing issues predict lower scores on EF performance measures among autistic children (Pastor‐Cerezuela et al, 2020). It is perhaps not surprising then that although EF difficulties are observed in both the home and school setting for autistic children, researchers have found evidence for a widening gap with age in actualised EF ability between autistic and neurotypical groups in the school setting, but not the home setting (Tschida & Yerys, 2022). Further, research indicates that autistic children have more variable observer‐reported EF scores across home and school settings compared with neurotypical samples (Tschida & Yerys, 2022), while teachers report greater EF difficulties for children with ADHD compared with their parents (Mares et al, 2007; Soriano‐Ferrer et al, 2014), indicating that neurodivergent children's EF performance is more vulnerable to poor environmental fit, and/or that they are more likely to experience differences in the degree of environmental fit between home and school compared with neurotypical peers.…”
Section: Individual Differences In Responses To the Environment: A Fo...mentioning
confidence: 99%
“…There is more information on the possible dysfunction at the EF level in people with autism in the domestic context than in the educational environment [10], denoting that the perception of teachers and parents suggests that they tend to underestimate the EF [6,11].…”
Section: Introductionmentioning
confidence: 99%